Acute Necrotizing Encephalopathy: An Underrecognized Clinicoradiologic Disorder - Xiujuan Wu; Wei Wu; Wei Pan; Limin Wu; Kangding Liu; Hong-Liang Zhang (Mediators of Inflammation)
Acute necrotizing encephalopathy (ANE) is a rare but distinctive type of acute encephalopathy with global distribution. Occurrence of ANE is usually preceded by a virus-associated febrile illness and ensued by rapid deterioration. However, the causal relationship between viral infections and ANE and the exact pathogenesis of ANE remain unclear; both environmental and host factors might be involved. Most cases of ANE are sporadic and nonrecurrent, namely, isolated or sporadic ANE; however, few cases are recurrent and with familial episodes. The recurrent and familial forms of ANE were found to be incompletely autosomal-dominant. Further the missense mutations in the gene encoding the nuclear pore protein Ran Binding Protein 2 (RANBP2) were identified. Although the clinical course and the prognosis of ANE are diverse, the hallmark of neuroradiologic manifestation of ANE is multifocal symmetric brain lesions which are demonstrated by computed tomography (CT) or magnetic resonance imaging (MRI). The treatment of ANE is still under investigation. We summarize the up-to-date knowledge on ANE, with emphasis on prompt diagnosis and better treatment of this rare but fatal disease.